2017
DOI: 10.1108/ci-06-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Architects’ perception of the innovativeness of the Swedish construction industry

Abstract: Purpose The aim of this paper is to enhance the understanding of architects’ perceptions of the propensity to adopt innovations in building construction. Design/methodology/approach Based on a theoretical underpinning of the multilevel perspective on socio-technical transitions, a web-based questionnaire (n = 412) was used to empirically investigate Swedish architects’ perceptions of innovativeness in the building construction industry. Specifically, the study looks at perceptions of the level of innovativen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…This signal is important as a majority of building industry actors are unwilling to go beyond legal standards without additional policy pressure (Ryghaug & Sørensen 2009). Earlier Swedish research shows that strong policies are needed to encourage actors to develop sustainable buildings as the Swedish construction sector is strongly locked-in to traditional practices (Hemström et al 2017). If advocates of passive houses would have been stronger in the policy-making process, this would have been a key mainstreaming activity -a passive house standard established through law.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…This signal is important as a majority of building industry actors are unwilling to go beyond legal standards without additional policy pressure (Ryghaug & Sørensen 2009). Earlier Swedish research shows that strong policies are needed to encourage actors to develop sustainable buildings as the Swedish construction sector is strongly locked-in to traditional practices (Hemström et al 2017). If advocates of passive houses would have been stronger in the policy-making process, this would have been a key mainstreaming activity -a passive house standard established through law.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…to technology adoption by some authors (Ramilo and Embi, 2014;Skibniewski, 2014) which include (Cory and Bozell, 2001;Jones and Saad, 2003;O'Sullivan, 2002 Much of this research affirmed that technological advancement of the digital technologies has the potential to improve cost, quality and productivity significantly (Gambatese and Hallowell, 2011;Ramilo and Embi, 2014). However, some studies show that significant technical and organizational barriers exist, that impede the effective adoption of these technologies (Ozorhon et al, 2010;Ramilo and Embi, 2014;Hemstrom et al, 2017). A Malaysian industry-wide survey found risk and liability, high equipment cost, financial disincentives, inadequate R&D investment, lack of capable people, inadequate technology transfer, inflexible building codes and standards, and lack of governmental support as major challenges to new ideas (Civil Engineering Research Foundation, 1996;Romilo and Embi, 2014).…”
Section: Digital Innovation In Context and Barriersmentioning
confidence: 95%
“…In Ozorhon et al's (2010) report, economic conditions and availability of financial resources are clearly seen as two top barriers to the adoption/implementation of innovative technology in the UK. Similarly, with architects' perception of the Swedish construction industry, Hemstrom et al (2017) indicated financial issues as barriers to the innovativeness of the industry. Thus, financial implications play a significant role in digital technology development.…”
Section: Digital Innovation In Context and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of the manufacturers of glulam was increasing worldwide [25] as well as in the Baltic countries [17], [18]. At the same time, the number of construction projects [15] using glulam was increasing and getting bigger, higher and more complex.…”
Section: Introductionmentioning
confidence: 99%